Three stitch hernioplasty: A novel technique for beginners - Manikandan Patchayappan; Sangara Narayanan Narayanasamy; Nagarajan Duraisamy (Avicenna Journal of Medicine, 2015)
Objective: To analyze mesh fixation with minimum sutures and postoperative complications. Study Design: Prospective study. Place and Duration of Study: Department of General Surgery, Thanjavur Medical College and Hospital, Tamil Nadu, from July 2010 to June 2012. Materials and Methods: All inguinal hernia patients, who fulfilled the sample selection criteria, were admitted and planned for surgery. The prolene mesh is fashioned as in Lichtenstein's repair, placed and fixed only by three prolene stitches. The first stitch is made in the periosteum of pubic tubercle. The second stitch is taken in the inguinal ligament (1.5 cm lateral to the pubic tubercle) and the third stitch is from the medial most part of the conjoint tendon, that is, the mesh is fixed in the medial aspect alone. Results: Majority of the patients fall between the age group of 40 and 60 (72%) years and all are male patients. Of the total cases, 50% were right sided, 25% were left sided, and 25% were bilateral. Of the postoperative complications, 12% had seroma, 4% had hematoma, 2% developed surgical site infection, 2% developed chronic groin pain, 1% presented with recurrence, and none developed foreign body sinus. Conclusion: The incidence of long-term complications of three stitch hernioplasty are comparable to that of the other standard, tension-free open hernia repair as well as other laparoscopic procedures. Moreover, the three stitch hernioplasty method is a simple method, easy for the beginners to adopt, has less foreign body reaction, less time consuming, causes less tissue trauma, and lesser chance for vascular injury.